2014
DOI: 10.1021/nl501413t
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot Opto-Mechanics in a Fully Self-Assembled Nanowire

Abstract: We show that optically active quantum dots (QDs) embedded in MBE-grown GaAs/AlGaAs core-shell nanowires (NWs) are coupled to the NW mechanical motion. Oscillations of the NW modulate the QD emission energy in a broad range exceeding 14 meV. Furthermore, this opto-mechanical interaction enables the dynamical tuning of two neighboring QDs into resonance, possibly allowing for emitter-emitter coupling. Both the QDs and the coupling mechanism, i.e. material strain, are intrinsic to the NW structure and do not depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
112
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 49 publications
4
112
1
Order By: Relevance
“…Numerical calculations following the same method as used in Ref. 6 confirm that these resonances indeed correspond to the fundamental flexural modes of the singly clamped nanowires.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Numerical calculations following the same method as used in Ref. 6 confirm that these resonances indeed correspond to the fundamental flexural modes of the singly clamped nanowires.…”
mentioning
confidence: 56%
“…Furthermore, the wide choice of nanowire growth material and the possibility to grow nanowire heterostructures could allow access to different measurement modalities, such as sensing of local electric or magnetic fields. In recent experiments, 5,6 coupling of optical transitions of a self-assembled quantum dot embedded in a nanowire to the motion of the nanowire through strain was demonstrated, opening the way to investigation of hybrid devices with nanowires as their main building blocks. Nanowire heterostructures are attractive as hybrid systems, as they can combine multiple functionalities in one integrated structure.…”
mentioning
confidence: 99%
“…The subsequent emergence of nanomechanical oscillators and evolutions in readout techniques [2][3][4] lead to impressive improvements in force sensitivity [5], enabling detection of collective spin dynamics [6][7][8], single electron spin [9], mass sensing of atoms [10,11] or inertial sensing [12]. Attractive perspectives arise too when nanoresonators are hybridized to single quantum systems, such as molecular magnets [13], spin or solid states qubits [14][15][16][17]. This reduction of the probe size naturally motivates the exploration of force fields on dimensions smaller than their characteristic length scale where a great physical richness is expected, in particular for nanoscale imaging or investigations of fundamental interactions such as proximity forces or near field couplings.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The integration of QDs in one-dimensional crystals (nanowires, NWs) has increasingly gained interest because of the improvement in the photon extraction efficiency and overall functionality. [10][11][12][13][14][15][16][17][18][19] Recently, it has been shown that self-segregation processes in ternary Al x Ga 1Àx As shells lead to the observation of luminescence stemming from 3D confined excitons. Several high-resolution imaging methods have demonstrated that the Al x Ga 1Àx As shells are indeed not homogeneous and contain nanoscale Ga-rich islands.…”
mentioning
confidence: 99%